Effects of altitude on the soot emission and fuel consumption of a light-duty diesel engine - Ghazikhani, Mohsen; Feyz, Mohammad E.; Mahian, Omid; Sabazadeh, Ali (Transport, 2013)
A four-cylinder, direct-injection (DI) diesel engine was used to study the effects of altitude on the variations of the exhaust soot emission and engine performance. The experiments were conducted in Mashhad, Iran, at an altitude of 975 m above sea level. A three-lobe rotary blower of Roots type was employed in order to simulate the altitudes down to 350 m by increasing the inlet manifold pressure of the engine. The tests were performed based on the ECE-R49 test cycle, and for each testing point, the experiments were repeated for five boosting pressures which correspond to five different altitudes. Results indicate that with increasing the altitude from 350 m to 975 m, the soot emission increases about 40%. This increase is due to the relatively lower the air density introduced into the cylinders in higher altitudes that leads to the increase of autoignition delay time which could shorten the late combustion phase; hence, the soot burnout process deteriorates. Also it was found that at low engine loads, the Brake-Specific Fuel Consumption (BSFC) increases about 20% with raising the altitude from 350 m to 975 m. At higher loads, the raising rate of fuel consumption is insignificant. The effects of altitude on the other engine parameters such as induced air mass flow rate, volumetric efficiency, equivalence ratio, and exhaust temperature were investigated as well. In addition, a sensitivity analysis was conducted and the results revealed that among the engine parameters, the soot emission alteration has the most sensitivity to the change of the altitude. First Published Online: 16 Jul 2013